Comparing Rates of Multiple Chronic Conditions at Primary Care and Mental Health Visits to Community Health Centers Versus Private Practice Providers. Issue 2 (April 2020) - Corallo, Bradley; Proser, Michelle; Nocon, Robert
Abstract : This study identifies differences in rates of multiple chronic conditions at primary care and mental health visits to Community Health Centers and private practice providers using 2013 National Ambulatory Medical Care Survey data. Community health center visits had higher rates of 1 or more, 2 or more, and 3 or more chronic conditions for working-age patient visits (ages 18-64). There were no differences in other age groups. After controlling for age and other covariates using logistic regression, community health center visits had 35% higher odds of having any chronic condition and 31% higher odds of having 2 or more chronic conditions.